The role of wildlife in the epidemiology of tick-borne diseases in Slovakia - Kazimírová, Mária (2024)
Tick-borne diseases (TBD) represent an important challenge for human and veterinary medicine. In Slovakia, studies on the epidemiology of tick-borne pathogens (TBP) with regard to reservoir and amplifying hosts have focused on small mammals and to a lesser extent to birds or lizards, while knowledge on the role of remaining vertebrate groups is limited. Generally, wild ungulates, hedgehogs, small and medium sized carnivores, or squirrels are important feeding hosts for ticks and serve as reservoirs for TBP. Importantly, as they carry infected ticks and/or are serologically positive, they can be used as sentinels to monitor the presence of ticks and TBP in the environment. With their increasing occurrence in urban and suburban habitats, wild ungulates, hedgehogs or foxes are becoming an important component in the developmental cycle of the vector tick Ixodes ricinus and of TBP such as Anaplasma phagocytophilum or Babesia spp. On the other hand, it has been postulated that cervids may act as dilution hosts for Borrelia burgdorferi s.l. and tick-borne encephalitis virus. In southwestern Slovakia, a high prevalence of infection with Theileria spp. (100%) was observed in Cervidae, while A. phagocytophilum (about 50%) was detected in Cervidae and wild boars. The following pathogens were detected in ticks feeding on free-ranging ungulates, birds, and hedgehogs: Rickettsia spp., Coxiella burnetii, Neoehrlichia mikurensis, B. burgdorferi s.l., and Babesia spp. The growing understanding of the role of wildlife as pathogen reservoirs and carriers of pathogen-infected ticks offers valuable insights into the epidemiology of TBP, providing a foundation for reducing the risk of TBD.